2018
DOI: 10.12788/jhm.3086
|View full text |Cite
|
Sign up to set email alerts
|

Acute Treatment of Hypertensive Urgency

Abstract: The "Things We Do for No Reason" (TWDFNR) series reviews practices which have become common parts of hospital care but provide little value to our patients. Practices reviewed in the TWDFNR series do not represent "black and white" conclusions or clinical practice standards but are meant as a starting place for research and active discussions among hospitalists and patients. We invite you to be part of that discussion. CLINICAL SCENARIOA 67-year-old man is hospitalized with community-acquired pneumonia. He has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Whereas prior studies examined proxies for hypotension-related harms, such as hypotension, rapid reduction in BP, tachycardia, or the need to provide IV fluids, our study, to our knowledge, is the first to directly assess end-organ damage, including AKI, myocardial injury, and stroke. Our finding that the harms associated with treatment persist into higher intervals of BP, even those categorized as hypertensive urgency, strengthens the case for conservative management . Moreover, although prior studies have described harms with IV treatment, we included oral and IV agents and analyzed outcomes by route .…”
Section: Discussionmentioning
confidence: 77%
“…Whereas prior studies examined proxies for hypotension-related harms, such as hypotension, rapid reduction in BP, tachycardia, or the need to provide IV fluids, our study, to our knowledge, is the first to directly assess end-organ damage, including AKI, myocardial injury, and stroke. Our finding that the harms associated with treatment persist into higher intervals of BP, even those categorized as hypertensive urgency, strengthens the case for conservative management . Moreover, although prior studies have described harms with IV treatment, we included oral and IV agents and analyzed outcomes by route .…”
Section: Discussionmentioning
confidence: 77%
“…The patient’s target BP should not be set at a level much lower than the baseline BP [ 1 ]. In real-world practice, treatment of HTN-U has varied, ranging from prescribing medications for treating potential secondary causes such as pain or drug withdrawal to resting for at least 30 minutes [ 7 ]. A study found that among 379 patients who presented to the clinic with HTN-U, those referred to the ED and those sent home had similar rates of major adverse cardiovascular events [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 The in-hospital and one-year mortality for a hypertensive emergency are 13% and 39%, respectively. 17 These data demonstrate that hypertensive emergencies have both short-and long-term risks. 17 limits.…”
Section: Discussionmentioning
confidence: 83%